Kendala dan strategi operasi penangkapan ikan alat tangkap bubu di Muara Angke, Jakarta: Constrains and fishing operation strategy of traps in Muara Angke, Jakarta - Eko Sri Wiyono (Fakultas Perikanan dan Ilmu Kelautan, Universitas Mulawarman, 2022)
Compared to other businesses, fishing is a high-risk economic activity. To minimize risk, it is necessary to the management of fishing operations. Due to limited capital and fish resources, the goal of fishing operations management is to minimize operating costs and maximize capture catches. However, understanding the strategy of fishing operations is rarely understood and considered less important. To understand the strategy of fishing operations, a study has been conducted in Muara Angke, Jakarta. The aims of this study are to analyze the constraints of fishing operations and adaptation strategies which developed by fishermen trap in fishing operations. The results suggest that there are three major constraints faced by the fishing traps in the arrest operation, namely climate, fishing season and venture capital. In response to the constraints and issues, the fisherman traps are still carried out regular fishing strategy.